Pengaruh Penggunaan Gadget Terhadap Ketajaman Penglihatan Murid Kelas 6A Di SD Negeri 149 Pekanbaru - Ermi Yusfita (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
The use of gadgets has become an integral part of daily life for elementary school children. This study aims to examine the impact of gadget usage on visual acuity among Grade 6A students at SD Negeri 149 Pekanbaru. The research was conducted from July 22 to 24, 2024, using a quantitative descriptive approach. A total of 39 students were selected through total sampling. Data were collected via questionnaires and analyzed using descriptive statistics with percentage formulas. The findings revealed that 87% of students used gadgets for extended periods, 82% used gadgets while lying down or prone, and 74% frequently watched television. In contrast, only 15% of students wore glasses as a corrective measure, and none used contact lenses. Most students relied on nutritious food consumption, such as fruits and vegetables (92%), to maintain eye health. The study concludes that gadget usage contributes to a decline in visual acuity, and this behavior warrants special attention from schools, parents, and healthcare professionals.